Green Investment and Financial Performance: Analysis of the Impact of Sustainable Investment - Ida Ayu Putu Megawati; Ni Nengah Rupadi Kertiriasih; Made Ratih Nurmalasari; Putu Putri Prawitasari; Ni Putu Ari Krismajayanti (Oikonomia : Journal of Management Economics and Accounting, 2026)
This study investigates the relationship between green investment and corporate financial performance, analyzing the impact of sustainable investment practices on key financial indicators including Return on Assets (ROA), Return on Equity (ROE), and Tobin's Q. As environmental concerns grow and regulatory frameworks tighten globally, firms are increasingly allocating resources toward environmentally sustainable activities. Drawing upon a systematic review of 20 peer-reviewed studies published between 2018 and 2025, this research synthesizes evidence on whether green investments translate into measurable financial gains or represent a cost burden for firms. The analysis encompasses diverse industries and geographic contexts, including Indonesia, Europe, Ireland, and global markets. Findings reveal that green investment generally yields a positive effect on financial performance, particularly in the long run, though the magnitude varies by industry, firm size, and institutional environment. Environmental, Social, and Governance (ESG) disclosure quality and corporate social responsibility (CSR) practices are identified as significant mediating factors. Green financing instruments such as green bonds also contribute to enhanced corporate performance. This study contributes to the growing body of sustainable finance literature by providing a comprehensive overview of mechanisms linking green investment to financial outcomes and offers.